PANDA: a software for polyhedral transformations - Lörwald, Stefan; Reinelt, Gerhard (EURO journal on computational optimization, 2015)
In this paper, we present the software Parallel AdjaceNcy Decomposition Algorithm (PANDA), an efficient implementation of the vertex and facet enumeration problem for polyhedra. The software is based on the double description method. Special features are the possibility to employ the so-called adjacency decomposition, the option of doing computations in exact integer arithmetic, the exploitation of symmetry information and the easy usability of parallel hardware. With computational experiments, we demonstrate the effectiveness of the software.
Gesehen am 03.06.2020